Desenvolvimento de hidromel gaseificado naturalmente - Fortes, Juciane Prois (2017)
Mead is a fermented beverage obtained by diluting honey into water with added nutrients and yeast. In some regions of Europe it is a much consumed and appreciated drink, in Brazil, however, it is little known and exploited. The increase in the demand for new biotech products in the food area, such as the development of new honey-based products, can be an important alternative to the flow of production and at the same time an interesting way of adding value to the product. The objective of the present study was to develop and characterize a naturally gaseous mead. Two types of honey were used, wild honey and orange honey, being the physical chemical characterization of the honey. The results of the characterization showed that the raw material presented a quality standard and identity characteristic of the pure honey of bees (Appis mellífera). Knowing the quality of the raw material, three different meads were elaborated: with wild honey, with honey of orange tree and the combination of the two honeys in the proportion of 1: 1. The final mead products mead and gassed mead naturally were characterized by physical-chemical analyzes of phenolic compounds and antioxidants. Among the two products, total acidity contents of the aerated mead presented an increase in relation to the base mead, where the total acidity is slightly higher with wild honey representing around 6.9% more acid than the orange honey as well as the combination of honeys as well as fixed acidity. The consumption of total sugars in the first fermentation for ethanol production ranged from 82.7 to 85.8% and in the second was relatively lower, but the final alcohol content of the two products was 10.6% (v / v). The dry extract contents ranged from 20.18 to 25.86 g L-1 defining the gaseous mead as full-bodied beverages. Both the base mead (179.72 to 213.77 mg EAG L-1) and the gaseous mead (203.40 to 223, 83 mg EAG L-1) presented relevant contents of total polyphenols in their composition. For antioxidant activity by the ABTS radical the base mead with orange honey presented higher antioxidant activity, but already in the aerated mead the highest content was found for the combination of the honeys. Considering that the different types of gaseous mead obtained in the present study had physical chemical characteristics that met the quality standards established by the legislation for mead, a sensorial evaluation of the respective beverages was carried out, through the ordination test, which did not present a 8 significant difference between the meads. The acceptance test showed that the aerated mead of orange honey obtained the highest scores, even though it did not present a difference in all the attributes. Therefore, naturally metered mead is a viable product with good acceptance regardless of the type of honey.